Analisis Model Peluang Kecelakaan Sepeda Motor dengan Big Five Personality - Kore, Desri M. Hale; Djahamouw, Putri D. K; Artati, Mardiana (Syntax Corporation, 2025)
Traffic accidents occur due to many factors, one of which is the human factor which is the main cause but is still often ignored. This study was conducted to determine the influence of human characteristics and personality on a person's chances of experiencing a motorcycle accident. The results of the analysis of the structural equation modeling and multinomial logistic regression methods were obtained from a one-time accident probability model Log P = -0.977 – 21.33X31 – 2.42 X32 – 1.401X5.31 and a more than one accident chance model Log P = -0.108 – 21.33X31 + 0.481X5.22 + 0.181X6.52 + 0.292X7.4. Primary school education level, junior high school education level, brake and motorcycle light checks, chatting while driving and personality neuroticism (pre-pandemic) have a significant influence on the chances of accidents either once or more than once. From this relationship, it can be concluded that there is a need for prevention to minimize the accident rate such as early introduction of traffic safety, the importance of vehicle inspections, good and correct driving attitudes and the existence of psychological tests for personality.